Main Reasons for Using of PPP Contracts in Health Sector: An Analytical Study - Aqeel Salahuddin Mahdi Al-Shadeedi; Angham E. A. Al-Saffar; Azhar Hussein Salih (Salehan Institute of Higher Education, 2019)
The health sector in Iraq had faced enormous challenges. The health care system suffered a catastrophic deterioration under the former regime. The 1991 Gulf war incurred Iraq’s major infrastructures huge damages; includes health centers, clinics, hospitals, etc. The United Nations economic sanctions aggravated the deterioration process. The level of health care in Iraq has dropped markedly as the government budget allocated to the Ministry of Health (MOH) had decreased from 450 million in 1970 to about 250 million in 1985 then the annual total health budget for the ministry, a decade after the sanctions had fallen to 22 million which is barely 5% of what it was in the 1970s. On the other hand, the conflict of 2003 destroyed an estimated 12 percent of hospitals. Moreover, the war at 2014 held on ISIS-led to almost total destruction in most hospitals in the Central and Northern provinces. All this requires a quick strategy to advance the health sector and create a sustainable health sector. The researchers in this study will demonstrate, what are the pros and cons of Public-Private Partnership (PPP) contracts, how can be used in the Iraqi health sector, the main causes of dependence the MOH to using the PPP contracts in the all existing and the unfinished hospitals.